Oxygen uptake in relation to body weight in freshwater fish Tilapia Oreochromis niloticus (Our Nature, 2025)
This study shows the oxygen uptake rates of Tilapia (Oreochromis niloticus), in relation to body weight during two distinct seasonal temperature conditions: winter (20±1°C) and summer (30±1°C). The relationship between oxygen consumption (mlo2/hr) and body weight was analyzed using the equation y=a.Wb, where (a) is the intercept and (b) is the regression coefficient. In winter, the regression coefficient (b) was 0.7038, with a correlation coefficient (r) of 0.9972 (p